Expertise and Service: A Call to Action - Butler, Rebecca (Theological librarianship, 2014)
Although theological librarianship occurs most often at seminaries or graduate level theology programs, there are also librarians working with theology on an undergraduate level. In many cases, these librarians are responsible for additional subject areas and may or may not have any theological expertise or training. While the two groups do the same types of work, they are doing so in different ways. To explore these commonalities and differences, a study was conducted among undergraduate theology liaisons and those results were compared with the literature and data regarding graduate level theological librarianship. One hundred ten undergraduate librarians responded to a survey regarding theological liaison activities, and the results indicate both the need for more research and the need for further emphasis on undergraduate subject-area liaison duties in theology and adjacent areas